Aplikasi Informasi Wisata Kota Jember Berbasis Mobile Dengan Dukungan Info Transportasi Dan Fasilitas Umum - Aldio Tripadana; Adi wibowo; Justinus Andjarwirawan (Jurnal Infra, 2017)
Indonesia is a country known for many tourist attractions and a unique culinary every area, both by tourists in the country and abroad. It makes a lot of tourists who arrived in large numbers to the site every year. East Java is a province that is known for having a lot of tourist attractions and culinary most visited by tourists. One in East Java is a famous tourist town of Jember.Many tourists who come to the city of Jember to visit tourist attractions and culinary tasting, culinary. However, tourists do not get the tourist attractions in the town of Jember difficulty finding tour of the place in the town of Jember. Travelers also difficult to find a public place such as a hospital. This led to difficulties travelers looking for travel information and transportation to places of tourist and culinary desired destination.The conclusion of this application is the internet connection which adversely affects the performance of applications, such as sending data to a server or retrieve data from the server so slow load data and images. Testing minibus service 5 times menunujukan trial route to the destination successfully. Applications can provide a list of travel and search sites. The results of the questionnaire that has been done is the percentage of votes against the program interface users are 80% said regular interface, 20% said less interface. Percentage of votes to ease the program was 60% say the ease of taking the usual applications, 20% said the usual, 20% say excellent. The percentage of votes against the program's features are 60% said regular features, 40% said good features